PENGGUNAAN CONCEPTUAL CHANGE TEXT DENGAN MODEL PEMBELAJARAN 5E UNTUK MENGATASI MISKONSEPSI SISWA PADA MATERI ASAM BASA DI SMAN 4 TAMBUN SELATAN - Utami, Dyah Budi; Rahmawati, Yuli; Slamet, Riskiono (LPPM Universitas Negeri Jakarta, 2017)
This study aimed for exploring the integration of conceptual change text with 5E learning model to overcome students misconceptions about acids and bases in SMAN 4 Tambun Selatan. The research employed qualitative research approach with classroom action research conducted in XI IPA 3. Data are collected through CCT, interview, observation dan reflective journal to indetification students misconceptions and conceptual change. In this research students misconceptions in acid base concept, characteristic of acid base solutions, acid base indicators, ionization of strong and weak acids, ionization of strong and weak base, pH value and reaction between acid solution with base solution. The data analysis and interpretation indicates that in the first cycle there’s 90% students that have partial understanding category, in the second cycle there’s 83% students that have sound understanding category and in the third cycle there’s 88% students that have sound understanding category. The findings lead to recommendation to use conceptual change text with 5E model to overcome student misconception and fostering conceptual change. Other implication of this research is students should understanding concept by drawing their own mental models. Keywords: Acids and Bases, Classroom Action Research, Conceptual Change Text, 5E Learning Model, Student Misconception